The influence of stress control training on interpersonal relationships in the workplace - Sadir, Maria Angélica; Novaes Lipp, Marilda (O Mundo da Saúde, 2013)
Stress has become a common problem in the workplace. The consequences are increase in absenteeism, lower productivity and interpersonal difficulties. The aim of this study was to determine the impact of a Stress Management Training Program, focused on interpersonal relationships at work (TCS-RI) and to compare individual with group treatment effects. Twenty-nine adults were the participants, 17 of them received treatment in group while 12 were treated individually. The training was identical for all participants in that it covered the same specific topics in each of the ten sessions. Participants were interviewed and tested before and after training using the Lipp Stress Symptoms Inventory, the Social Skills Inventory and a Interview about the relationship. Results showed that the TCS-RI was effective in improvement in the participants’ social skills. At the end of the training, interpersonal relationships were perceived as being more gratifying and less problematical. It may be concluded that interpersonal social skills may be acquired in a relatively short period of time (10 weeks) when the TCS-RI is used.